The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/pssb.200778595
|View full text |Cite
|
Sign up to set email alerts
|

Atom probe reveals the structure of InxGa1–xN based quantum wells in three dimensions

Abstract: The three‐dimensional atom probe has been used to characterize Inx Ga1–x N based multiple quantum well structures emitting from the green to the ultra‐violet with sub‐nanometre resolution over a 100 nm field of view. The results show gross discontinuities and compositional variations within the UV‐emitting quantum well layers on a 20–100 nm length scale. We propose that these may contribute to the high efficiency of this structure. In addition, the analysis shows the presence of indium in the barrier layers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Fluctuations in QW width have also been hypothesized to induce carrier confinement, [28][29][30]53,54 and subnanometer fluctuations have been identified in APT measurements of InGaN QWs on planar substrates. 33 Surfaces of constant concentration ("isoconcentration surfaces") were used to characterize individual QW interfaces in 3D (Figure 2c) without projection artifacts. The isoconcentration surfaces are generated with 1 nm 3 voxels to create surfaces that are continuous and border each QW on both sides without any connection between the individual surfaces.…”
mentioning
confidence: 99%
“…Fluctuations in QW width have also been hypothesized to induce carrier confinement, [28][29][30]53,54 and subnanometer fluctuations have been identified in APT measurements of InGaN QWs on planar substrates. 33 Surfaces of constant concentration ("isoconcentration surfaces") were used to characterize individual QW interfaces in 3D (Figure 2c) without projection artifacts. The isoconcentration surfaces are generated with 1 nm 3 voxels to create surfaces that are continuous and border each QW on both sides without any connection between the individual surfaces.…”
mentioning
confidence: 99%
“…This causes a spatial separation of electron and hole wave functions within InGaN quantum wells (QWs), reducing the carrier radiative recombination rate and internal quantum efficiency (IQE). , Such effects can be avoided by growing along nonpolar orientations, such as the a -axis, but a -axis GaN films exhibit high stacking fault and dislocation densities on common substrates such as sapphire or silicon, resulting from large lattice mismatches. These defects can act as nonradiative recombination centers that degrade IQE. In contrast to thin films, a -axis nanowires can be grown virtually free of dislocations due to the small substrate interfacial area and termination of dislocations at the nanowire surface. , In addition, a core–shell nanowire geometry allows for high light extraction due to the large junction area and increased directionality of light emission. …”
mentioning
confidence: 99%
“…It is especially challenging to perform APT of GaN because of its low electrical conductivity; a pulsed laser is required to achieve reliable evaporation, and the mass resolution is degraded by the poor thermal conductivity . In spite of these challenges, APT has been used to analyze dopant clustering and map interface uniformity in planar InGaN QWs, , GaN–AlGaN superlattice structures, and c -axis GaN nanowires . The latter study, using a 532 nm pulsed laser, reported variations in the evaporation behavior of Ga and N ions that was attributed to nonuniform heating at the nanowire tip.…”
mentioning
confidence: 99%
“…Recently large fluctuations of the quantum well width with a strip like geometry have been reported in a two temperature process (2 T ) and detected by conventional TEM, atomic force microscopy (AFM) and high angle annular dark field (HAADF) STEM 5, 6. These fluctuations were also studied by three‐dimensional atom probe tomography (APT) 7, with which method the existence of the short range indium clustering was excluded. In contrary this type of clustering has been confirmed in Ref.…”
Section: Introductionmentioning
confidence: 99%